(3GdaUhUs - (3UGYO Hf GdMSf Hf YjSi GdQHYj GdHZOGOj, CHh GdYdGA,J (B417 (3g` s
(3ChdgG (B:s
(3CadM GeQD MeO QHg Ydi fYeg hCf LeGd GdeQA Ydeg Yf GdfHi Udi Gddg Ydjg hSde ef cJe YdekG GdLeg Gddg HdLGe ef GdfGQ s
(3BNQgG (B:s
(3jfJgi Hbhdg Udi Gddg Ydjg hSde (B: (3hef bGd eQI (B: (3dG Edg EdG Gddg ONd GdLfI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B186 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B318s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs